Аналіз життєвих форм ефіроолійних рослин за типом кореневої системи в умовах південного сходу України - Gorlacheva, Z.S.; Kustova, O.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The ratio of biomorphs according to the type of root system in introduced species from the collection of essentialoil plants of the Donetsk Botanical Garden of the NAS of Ukraine was analyzed. A combined or intermediate type of the root system being adapted to the arid conditions of the South-East of Ukraine is predominant.